A case of cutaneous toxigenic Corynebacterium ulcerans likely acquired from a domestic dog. Issue 7 (30th September 2019) - Othieno, Richard; Mark, Kate; Etherson, Michelle; Foster, Geoffrey; Murray, Steven; Kalima, Pota; Fry, Norman K.; Cameron, Claire; Strachan, Jenni
Abstract : Introduction. Corynebacterium ulcerans can produce diphtheria toxin and although still rare, is now the predominant cause of toxigenic diphtheria infection in the UK, making this organism of great clinical and public health importance. Here we describe a cutaneous case, likely secondary to domestic animal contact. Case presentation. A 60-year-old female presented with a slow-healing finger-burn wound. A skin swab cultured Corynebacterium ulcerans, which was confirmed to be toxin producing. She resided with her partner and two dogs, one of which had a chronic skin lesion. Her most recent diphtheria vaccine was in 2009. Four close contacts were identified, two of whom were healthcare professionals, and nose and throat swabs were obtained. The patient was treated with clarithromycin (14 day course), diphtheria vaccine and excluded from work until completion of antibiotics and negative clearance swabs. Contacts were given erythromycin (7 day course), vaccinated and healthcare worker contacts excluded from work until swab negative. A veterinary practitioner swabbed the throats and a skin lesion of their dogs. One contact (partner of patient) and all dog swabs were positive. Partial allelic profiles from MLST supported an epidemiological link. The dogs were treated with antibiotics and antimicrobial skin wash. Repeat swabs for the index case, contact and both dogs were negative following treatment. Conclusion. This was a rare case of cutaneous diphtheria secondary to Corynebacterium ulcerans with domestic animals the most likely source, although human-to-human contact could not be excluded, with important human and animal public health implications.